Behavior Characteristics of Hazardous Gas and Scattering Coal Dust in Coal Storage Sheds - Mok-Lyang Cho; Ji-Soo Ha; Tae-Kwon Kim (Applied Sciences, 2021)
This study has comprehensively analyzed the ventilation system of an indoor coal storage shed using computational fluid dynamics (CFD). In addition, the effects of the plan to improve the ventilation system were investigated by synthesizing the results. First, the velocity of inlet wind entering through the natural ventilation system was measured. Then, the concentration of carbon monoxide inside the coal storage shed was measured at the spontaneous combustion of coal. The boundary conditions were set using the measurement results. The characteristics of carbon monoxide concentration, ventilation volume, and behavior of scattering dust were analyzed. According to the CFD analysis results, the upper recirculation strength increased as the flow rate of external air increased. The flow-stagnation area occurred on the center wall. In particular, the concentration of carbon monoxide was high in the flow-stagnation area. When the inflow velocity was 2.0 m/s, a risk of 30 ppm or more occurred in the area near the second-floor workspace and central retaining wall. When ventilation dropped sharply, coal dust emissions decreased to 14.5%. Thus, ventilation must be secured by installing a natural ventilation system, in case spontaneous ignition occurs in many cells or the ventilation sharply decreases. Finally, in order to improve the ventilation system, the effect on the additional installation of natural ventilation and the use of mobile blowers was analyzed. Finally, in order to improve the ventilation system, the effect on the additional installation of natural ventilation and the use of mobile blowers was analyzed. As a result of the analysis, we concluded that using a mobile blower is more effective than a method of additionally installing a natural ventilation device. Carbon monoxide may be locally diluted, and ventilation volume additionally secured.